Fabrication of γ-Fe2O3 Nanoparticles by Solid-State Thermolysis of a Metal-Organic Framework, MIL-100(Fe), for Heavy Metal Ions Removal - Shengtao Hei; Yan Jin; Fumin Zhang (Journal of Chemistry)
Porous γ-Fe2O3 nanoparticles were prepared via a solid-state conversion process of a mesoporous iron(III) carboxylate crystal, MIL-100(Fe). First, the MIL-100(Fe) crystal that served as the template of the metal oxide was synthesized by a low-temperature (<100°C) synthesis route. Subsequently, the porous γ-Fe2O3 nanoparticles were fabricated by facile thermolysis of the MIL-100(Fe) powders via a two-step calcination treatment. The obtained γ-Fe2O3 was characterized by X-ray diffraction (XRD), N2 adsorption, X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM) techniques, and then used as an adsorbent for heavy metal ions removal in water treatment. This study illustrates that the metal-organic frameworks may be suitable precursors for the fabrication of metal oxides nanomaterials with large specific surface area, and the prepared porous γ-Fe2O3 exhibits a superior adsorption performance for As(V) and As(III) ions removal in water treatment.